Chromosomal scale assembly of parasitic wasp genome reveals symbiotic virus colonization - Jérémy Gauthier (Nature Portfolio, 2021)
Jeremy Gauthier et al. present the chromosome scale assembly of the genome of the parasitic wasp C. congregata and show that bracovirus genes have colonized all ten chromosomes. Comparison with genome scaffolds of another wasp reveals a striking stability of these regions over ~53 million years, suggesting strong evolutionary constraints.